No evidence for blocking the return of fear by disrupting reconsolidation prior to extinction learning. (June 2016) - Klucken, Tim; Kruse, Onno; Schweckendiek, Jan; Kuepper, Yvonne; Mueller, Erik M.; Hennig, Juergen; Stark, Rudolf
Abstract: Fear extinction is a central model for the treatment of anxiety disorders. Initial research has reported that the single presentation of a conditioned stimulus prior to extinction learning can permanently block the return of fear. However, only few studies have explored this issue and could not always replicate the findings. The present study examined human fear extinction using a four-day design. On the first day, two neutral stimuli were paired with electrical stimulation (UCS), while a third stimulus (CS−) was not. Twenty-four hours later, one conditioned stimulus (CS+rem ) and the CS− were reminded once, 10 min before extinction learning, while the other conditioned stimulus (CS+non-rem ) was not presented prior to extinction learning. All stimuli were presented during extinction learning and during two re-extinction sessions (24 h and 6-months after extinction learning) without reinforcement. Blood oxygen level-dependent (BOLD) responses and skin conductance responses (SCRs) to both CS+ and the CS− were explored during acquisition, extinction, and in both re-extinction sessions. Regarding SCRs, the results showed that a single presentation of a conditioned stimulus did not block the return of fear during re-extinction: Fear recovery during re-extinction (24 h and 6-months after extinction learning) was observed for both CS+ compared with the CS− with no difference between CS+rem and CS+non-rem . Regarding BOLD-responses, no significant differences between CS+rem and CS+non-rem were found in region of interest (ROI)-analyses (amygdala, ventromedial prefrontal cortex) during extinction learning and both re-extinction sessions. Whole-brain analyses showed increased BOLD-responses to the CS+non-rem as compared to the CS+rem in several regions (e.g., middle frontal gyrus) during extinction learning and re-extinction (24 h after extinction learning). The present findings suggest that the effect of preventing the return of fear by disrupting reconsolidation seems to be a more labile phenomenon than previously assumed. Possible boundary conditions and implications are discussed.